2017
DOI: 10.1680/jgere.17.00009
|View full text |Cite
|
Sign up to set email alerts
|

Seismic analysis of pile in liquefiable soil and plastic hinge

Abstract: Liquefaction is one of the leading seismic actions that cause extensive damage to buildings and infrastructure during earthquakes. In many historic cases, plastic hinge formations in piles were observed at inexplicable locations. This project investigated the behaviour of piled foundations within soils susceptible to liquefaction by using numerical analysis carried out in Abaqus software in terms of plastic hinge development. Three different soil profiles were considered in this project that varied in the thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Table 1 provides foundation soil parameters from two studies: (Kang & Jie, 2017) and (Rostami et al, 2017) and were utilized in the finite element analyses. For non-liquefiable soil, parameters are derived from both studies, whereas liquefiable soil parameters are based solely on Rostami et al (2017).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 provides foundation soil parameters from two studies: (Kang & Jie, 2017) and (Rostami et al, 2017) and were utilized in the finite element analyses. For non-liquefiable soil, parameters are derived from both studies, whereas liquefiable soil parameters are based solely on Rostami et al (2017).…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 provides foundation soil parameters from two studies: (Kang & Jie, 2017) and (Rostami et al, 2017) and were utilized in the finite element analyses. For non-liquefiable soil, parameters are derived from both studies, whereas liquefiable soil parameters are based solely on Rostami et al (2017). Note that all these soil properties have different parameters, for instance, the nonliquefiable soil (NLS) layer of medium-dense silty sand (MDSS) is different from the liquefiable soil (LS) layer of MDSS.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ramirez et al [111] compared the predictive capabilities of PDMY02 and SANISAND platforms. Furthermore, Drucker-Prager [117] and Mohr-Coulomb plasticity [118] models are also soil constitutive modelling approaches in 3D analyses of soil-foundation systems.…”
Section: Two-and Three-dimensional Numerical Modellingmentioning
confidence: 99%
“…It was reported that the plastic hinge length of piles extending through liquefiable layers is about 1.4 times larger than that of non-liquefiable conditions. However, the location of plastic hinges can be affected by a variety of factors, such as material properties, pile length and thickness of the liquefied soil layer [118]. Wang and Orense [125] used a 2DBNWF finite element model implemented via Open Sees to analyse the response of raked pile foundations in liquefying ground.…”
Section: Two-and Three-dimensional Numerical Modellingmentioning
confidence: 99%